Changing the social environment in an elementary school to reduce dropout predictors for African American students - Edwards, Leah Rose (2011)
Dropping out of school is a serious problem in the United States, especially for African American students. School systems have implemented various prevention and intervention programs to reduce the dropout rate of African American students with only limited success. These programs have generally not included a focus on social climate. Research clearly indicates social climate is directly related to specific behavior and academic predictors of dropout especially for African American students. This study is an examination of an unintentional racism workshop for teachers in a public elementary school, designed to reduce dropout predictors in African American students. The unintentional racism workshop was designed to assist teachers in creating a less threatening environment for African American students while reducing dropout predictors such as low grades, high absences, and discipline problems. This research did not demonstrate significant improvements in student variables such as grades, number of absences, and number of discipline referrals, after one year of implementation, but it did provide important implications and recommendations about future research into dropout prevention programs for African American students.